THE USE OF MODERN ANALOGUES OF LUTEINIZING HORMONE RELEASING HORMONE IN THE HORMONAL THERAPY IN PATIENTS WITH PROSTATE CANCER - E. Yu. Safronova; A. A. Krasheninnikov; S. A. Sergienko; A. A. Kostin (Исследования и практика в медицине, 2017)
The urgency of the problem of prostate cancer (PC) remains extremely high due to the continued growth of morbidity and mortality from this disease. Despite the introduction of diagnostics with the use of prostate specific antigen (PSA) and the increase in the number of cases of detection of localized forms of the disease, frequency of detection in the primary treatment of patients with advanced and metastatic prostate cancer remains high. Therapy aimed at reducing testosterone levels in the body of the patient with metastatic prostate cancer is the gold standard of treatment, so surgical or pharmacological castration to reduce testosterone levels, are generally accepted methods of therapy. Hormone therapy (HT) using a pharmacological castration is the major and most commonly used method of treatment of patients with metastatic prostate cancer, the effectiveness of which is comparable with surgical castration. The article presents a review of studies that compared the effectiveness and side effects of HT with the use of surgical and medical castration, as well as the results of domestic studies evaluated the effectiveness of the application of the drug buserelin-domestic analogue of LHRH.